Prototype Sistem Keamanan Pintu Kandang Dan Pemberian Pakan Ternak Puyuh Otomatis Berbasis Mikrokontroler - Anisa Muhaimin; Mohammad Hafiz Hersyah (CHIPSET, 2022)
This research aims to build a system that can maintain the security of the cage, give feed quail automatically and weigh the weight of the feed by the needs of quail based on the time of eating quail per day. The system consisted of several components, namely fingerprint, SW- 420, buzzer, LED, relay, Arduino Uno, solenoid key, servo, RTC, and Load cell. Access is restricted by examining the authentication through a fingerprint on the fingerprint sensor. If access is granted, then the cage door will open. Otherwise, the door remain close, and if the door is tampered with or opened by force, the SW-420 will automatically detect vibration on the door and turn on the buzzer as a notification. On the part feeding, a separate container-shaped tube as feed storage will be mounted to the motor servo, and the load cell as a tool weighing the weight of the feed is mounted on the container. The servo spin (open) duration is adjusted by the load cell when weighing the feed coming out of the servo with the amount of feed out by the requirements set out in the range of 14-16 gr/session time. Feed that has weighed on the container is ready to be consumed by the quail.